Visual short-term memory load modulates the early attention and perception of task-irrelevant emotional faces - Yang, Ping; Wang, Min; Jin, Zhenlan; Li, Ling (Frontiers in Human Neuroscience, 2015)
The ability to focus on task-relevant information, while suppressing distraction, is critical for human cognition and behavior. Using a delayed-match-to-sample (DMS) task, we investigated the effects of emotional face distractors (positive, negative, and neutral faces) on early and late phases of visual short-term memory (VSTM) maintenance intervals, using low and high VSTM loads. Behavioral results showed decreased accuracy and delayed reaction times for high versus low VSTM load. Event-related potentials (ERPs) showed enhanced frontal N1 and occipital P1 amplitudes for negative faces versus neutral or positive faces, implying rapid attentional alerting effects and early perceptual processing of negative distractors. However, high VSTM load appeared to inhibit face processing in general, showing decreased N1 amplitudes and delayed P1 latencies. An inverse correlation between the N1 activation difference (high-load minus low-load) and RT costs (high-load minus low-load) was found at left frontal areas when viewing negative distractors, suggesting that the greater the inhibition the lower the RT cost for negative faces. Emotional interference effect was not found in the late VSTM-related parietal P300, frontal positive slow wave (PSW) and occipital negative slow wave (NSW) components. In general, our findings suggest that the VSTM load modulates the early attention and perception of emotional distractors.